1995
DOI: 10.1097/00000658-199506000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of c-erb B-2 and p53 Immunoreactivity in Patients with Adenocarcinoma of the Esophagus

Abstract: Although p53 protein overexpression is commonly observed in adenocarcinoma of the esophagus, its prognostic value appears limited. In contrast, c-erb B2 protein expression predicts a favorable response to therapy and improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
4

Year Published

1997
1997
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 20 publications
1
46
0
4
Order By: Relevance
“…Casson et al (20) reported a series of 61 patients in which p53 alterations (gene mutation and protein accumulation) occurred mainly in poorly differentiated adenocarcinoma which showed significantly reduced postoperative survival. However, Duhaylongsod et al (43) and Coggi et al (44) failed to find any association between p53 gene mutation or protein accumulation and survival in patients with esophageal adenocarcinoma. In this study, we found no correlation between p53 mutation or nuclear overexpression and clinicopathological parameters.…”
Section: Discussionmentioning
confidence: 97%
“…Casson et al (20) reported a series of 61 patients in which p53 alterations (gene mutation and protein accumulation) occurred mainly in poorly differentiated adenocarcinoma which showed significantly reduced postoperative survival. However, Duhaylongsod et al (43) and Coggi et al (44) failed to find any association between p53 gene mutation or protein accumulation and survival in patients with esophageal adenocarcinoma. In this study, we found no correlation between p53 mutation or nuclear overexpression and clinicopathological parameters.…”
Section: Discussionmentioning
confidence: 97%
“…This result is in line with the results of most previous studies. 28,31,32,36 The existence of several published papers reporting associations of HER-2 amplification/overexpression with both poor 24,35,42 and improved prognosis 25,30 also rather argue against an important prognostic role of HER-2 in esophageal cancers. The general absence of an association of HER-2 amplification or overexpression with clinical parameters of malignancy is in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Akamatsu et al [72] found HER-2 expression to be a predictor of chemoresistance in esophageal squamous cell carcinoma. In contrast, others have shown that HER-2 expression predicts a favorable response to chemo-or radiotherapy and thus improves survival [73]. The reasons for these contradictory results need to be addressed in future studies.…”
Section: The Role Of Her-2 In Esophageal Cancermentioning
confidence: 92%